2008
DOI: 10.1136/adc.2007.128132
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous abbreviations: an audit of abbreviations in paediatric note keeping

Abstract: Objective: To assess the frequency, nature and understanding of abbreviations in medical records. Design: Audit of abbreviation use and meaning in paediatric handover sheets and medical notes compared to two standards, the Trust Intranet Medical Dictionary (TID) and Mosby's Medical Dictionary (MMD). A selection of abbreviations was shown to healthcare professionals to examine interpretation of abbreviations. Setting: Large inner-city district general hospital, Birmingham, UK. Main outcome measures: Frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 3 publications
2
40
0
Order By: Relevance
“…Many studies of doctors’ written entries in medical records have been retrospective,2 3 7 8 making between-doctor comparisons difficult because the originating clinical information differs between entries. We controlled the auscultation findings presented to participants in order to compare their drawings in a way not possible with retrospective analyses of different clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of doctors’ written entries in medical records have been retrospective,2 3 7 8 making between-doctor comparisons difficult because the originating clinical information differs between entries. We controlled the auscultation findings presented to participants in order to compare their drawings in a way not possible with retrospective analyses of different clinical encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribers use abbreviations for convenience and to save time [81][82][83]. Sheppard et al revealed that 25 handover sheets and 108 medical notes contained over 221 types (2286 abbreviations) and 479 types (3368 abbreviations) of medical abbreviations respectively [84]. Another multicentre study carried out to evaluate the quality of prescription writing showed that abbreviations were used in more than 80% of prescriptions against 30% at one hospital that used electronic prescribing [85].…”
Section: Improving the Quality Of Hand-written Prescriptions To Avoidmentioning
confidence: 99%
“…An audit by the paediatric department at Birmingham Heartlands Hospital (Sheppard et al, 2008) recorded 221 different abbreviations amongst 2286 instances of abbreviation use on 25 handover sheets. Of these, only 14% were recognised by the Trust Intranet Medical Dictionary (TID) and 20% by Mosby's Medical Dictionary (MMD).…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Concern has been reported about the safe use of medical abbreviations in documents such as handover sheets and medical notes, especially when information is being communicated between staff of different specialties (BBC, 2008, Sheppard et al, 2008. This paper describes a study to investigate whether the use of symbols in handover documentation that is shared within and between multidisciplinary teams (MDTs) has similar safety implications.…”
Section: Introductionmentioning
confidence: 99%